2016
DOI: 10.1007/s10456-016-9513-x
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium-derived factor (PEDF): a novel trophoblast-derived factor limiting feto-placental angiogenesis in late pregnancy

Abstract: The rapidly expanding feto-placental vasculature needs tight control by paracrine and endocrine mechanisms. Here, we focused on paracrine influence by trophoblast, the placental epithelium. We aimed to identify differences in regulation of feto-placental angiogenesis in early versus late pregnancy. To this end, the effect of conditioned media (CM) from early and late pregnancy human trophoblast was tested on network formation, migration and proliferation of human feto-placental endothelial cells. Only CM of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 61 publications
2
20
0
Order By: Relevance
“…It is therefore crucial to understand the full potential of these bioassays during their specific applications. These assays have been instrumental in the study of vascular biology in growth and development [68] but also play a key role in the design, development, and evaluation of drugs that positively or negatively modulate vessel function for the treatment of many diseases [911]. Some examples of where the use of such bioassays has been imperative are: (1) the development of angiostatic drugs for the treatment of cancer, ocular diseases, and other pathologic conditions where angiogenesis is implicated and also angiogenic treatment strategies in ischemic cardiovascular disease [12, 13], (2) screening of natural anti-angiogenic compounds [14], (3) the efforts to design combination therapies including angiogenesis inhibitors [1520], (4) the unraveling of mechanisms regulating lymphangiogenesis [21, 22], (5) the interrelationship of angiogenesis and immunity [2325], (6) the development of imaging as diagnostic strategy [26], (7) the study of drug resistance mechanisms [2729], (8) development of compounds and strategies for the revascularization of ischemic injuries [30, 31], and (9) to improve the vascular fitness in aging vessels [32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore crucial to understand the full potential of these bioassays during their specific applications. These assays have been instrumental in the study of vascular biology in growth and development [68] but also play a key role in the design, development, and evaluation of drugs that positively or negatively modulate vessel function for the treatment of many diseases [911]. Some examples of where the use of such bioassays has been imperative are: (1) the development of angiostatic drugs for the treatment of cancer, ocular diseases, and other pathologic conditions where angiogenesis is implicated and also angiogenic treatment strategies in ischemic cardiovascular disease [12, 13], (2) screening of natural anti-angiogenic compounds [14], (3) the efforts to design combination therapies including angiogenesis inhibitors [1520], (4) the unraveling of mechanisms regulating lymphangiogenesis [21, 22], (5) the interrelationship of angiogenesis and immunity [2325], (6) the development of imaging as diagnostic strategy [26], (7) the study of drug resistance mechanisms [2729], (8) development of compounds and strategies for the revascularization of ischemic injuries [30, 31], and (9) to improve the vascular fitness in aging vessels [32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…Pigment epithelium-derived factor (PEDF) is a multifunctional paracrine protein that is a member of the serpin superfamily (14). PEDF is widely expressed in various tissues, including the placenta and trophoblast, and exerts anti-angiogenic effects in the late stages of pregnancy (15,16). Previous studies have revealed that activation of the NLRP3 inflammasome was inhibited by PEDF in ischemic cardiomyocytes through its phospholipaseA2/nutrin/patarin-like phospholipase domain-containing 2 PEDF receptor (PEDFR) (17).…”
Section: Introductionmentioning
confidence: 99%
“…After being incubated for 15 hours, the capillary-like structures were observed under a light microscope, and pictures of 3-5 visual elds/well were taken. The total length of the tubular structure was analyzed by using the Angiogenesis Analyzer plug-in for ImageJ software (NIH, USA) [36,37].…”
Section: In-vitro Matrigel Tube Formation Assaymentioning
confidence: 99%